PENGARUH KOMITMEN ORGANISASI DAN KOMITMEN PROFESIONALTERHADAP KEPUASAN KERJA AKUNTAN PUBLIK:ROLE STRESS SEBAGAI VARIABEL MODERATING - R. Ardi Agung Heriawan; Barbara Gunawan (Journal of Accounting and Investment, 2010)
The purpose of this research is to analyzed the influence of organizational commitment, professional commitment to job satisfaction of public accountants with a role stress as moderating variable. The samples of this research are 44 public accountants that worked at public accountants office which registered in Yogyakarta and Semarang. The data were analyzed by multiple regression method with moderating variable.The result of this analysis of individual test show that role conflict is not moderated of relation by organizational commitment with job satisfaction. Also with role ambiguity which not moderated or relation by organizational commitment with job satisfaction. The main practical implication of this research is that the public accountants organizational must be attention to jobs expectation of their auditors. Because that is the factors that rising the organizational commitment and in the future it will be to give a high school satisfaction.